2015
DOI: 10.1039/c5ra03913d
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis, characterization, and color-tunable luminescence properties of Bi2MoO6:Eu3+ phosphors

Abstract: Color-tunable Bi2MoO6:Eu3+ phosphors have been synthesized via a facile hydrothermal route followed by a further calcination treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Zou et al demonstrated that the Eu 3+ -activated Bi 2 MoO 6 phosphors could emit bright red emissions under UV light excitation. 30 It was also revealed that the Ba 2 ZnMoO 6 :Eu 3+ phosphors were suited for WLEDs as red-emitting phosphors. 31 Although some splendid performances have been gained in the RE ions activated molybdate phosphors, to extend their vivid applications in solid-state lighting, more endeavors should be made to further improve their luminescent properties.…”
Section: Introductionmentioning
confidence: 99%
“…Zou et al demonstrated that the Eu 3+ -activated Bi 2 MoO 6 phosphors could emit bright red emissions under UV light excitation. 30 It was also revealed that the Ba 2 ZnMoO 6 :Eu 3+ phosphors were suited for WLEDs as red-emitting phosphors. 31 Although some splendid performances have been gained in the RE ions activated molybdate phosphors, to extend their vivid applications in solid-state lighting, more endeavors should be made to further improve their luminescent properties.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Dexter mechanism the probability of energy transfer decreases as e -L and maximum typical distance was ~ 10 Å. According to Dexter theory, the decrease in PL intensity occurred as a result of the non-radiative energy transfer between Eu 3+ ions due to electric multipole-multipole interaction, which was distance dependent [22]. Blasse concluded that multipolar interactions were effective if the distance between Eu 3+ ions was larger than 5 Å; otherwise exchange interaction becomes dominant [23].…”
Section: Resultsmentioning
confidence: 96%
“…Figure 4B shows the PL emission spectra of LMO:Eu 3+ , Bi 3+ (λ ex = 466 nm). It consists of the multiple linear peaks corresponding to the 5 D 1 → 7 F 1 (536 nm), 5 D 1 → 7 F 2 (555 nm), 5 D 0 → 7 F 0 (580 nm), 5 D 0 → 7 F 1 (595 nm), 5 D 0 → 7 F 2 (614 and 625 nm), 5 D 0 → 7 F 3 (653 nm) and 5 D 0 → 7 F 4 (707 nm) electronic transitions of Eu 3+ ions 29,30 . The main excitation peak is attributed to the 5 D 0 → 7 F 2 electron transition of Eu 3+ ions.…”
Section: Resultsmentioning
confidence: 99%